2015
DOI: 10.1111/jeb.12606
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evolution in fluctuating environments: tolerance measurements at constant temperatures incorrectly predict the ability to tolerate fluctuating temperatures

Abstract: The ability to predict the consequences of fluctuating environments on species distribution and extinction often relies on determining the tolerances of species or genotypes in different constant environments (i.e. determining tolerance curves). However, very little is known about the suitability of measurements made in constant environments to predict the level of adaptation to rapidly fluctuating environments. To explore this question, we used bacterial clones adapted to constant or fluctuating temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 68 publications
2
68
0
Order By: Relevance
“…Allowing our populations to acclimate at a temperature regularly experienced during summer months in the wild (16°C; Table 1 and Supplementary material Fig. S1), measuring CT max in a fluctuating thermal environment (Ketola and Saarinen, 2015), increasing temperature at a rate previously found to be optimal for fish studies on thermal tolerance (0.3°C/min; Becker and Genoway, 1979) and measuring both CT max and a behavioural metric of agitation temperature have provided new evidence for less variability in thermal tolerance than previously thought. Reasons for this may be the scale at which other studies were conducted (see McDermid et al ., 2012; Stitt et al ., 2014) as well as the historical genetic or environmentally driven similarities in the populations being assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Allowing our populations to acclimate at a temperature regularly experienced during summer months in the wild (16°C; Table 1 and Supplementary material Fig. S1), measuring CT max in a fluctuating thermal environment (Ketola and Saarinen, 2015), increasing temperature at a rate previously found to be optimal for fish studies on thermal tolerance (0.3°C/min; Becker and Genoway, 1979) and measuring both CT max and a behavioural metric of agitation temperature have provided new evidence for less variability in thermal tolerance than previously thought. Reasons for this may be the scale at which other studies were conducted (see McDermid et al ., 2012; Stitt et al ., 2014) as well as the historical genetic or environmentally driven similarities in the populations being assessed.…”
Section: Discussionmentioning
confidence: 99%
“…, ; Phillips et al. ; Ketola and Saarinen ). Temperature is a major factor affecting species distributions, particularly of ectotherms (Angilletta et al.…”
mentioning
confidence: 97%
“…For example a study with ciliates showed no adaptation to fluctuating environments when measured at constant temperatures, but strains adapted to rapidly fluctuating thermal environments had increased expression of the heat shock protein Hsp90, indicating evolution of tolerance to cope with acute stress (Ketola et al, 2004). From studies that have tested the effect of evolution in fluctuating environments on tolerance curves and performance also in fluctuating environments (Bennett and Lenski, 1993;Leroi et al, 1994;Kassen and Bell, 1998;Hughes et al, 2007;Ketola and Saarinen, 2015), only one study shows a positive link between tolerance curve parameters obtained across constant environments and the performance in fluctuating environments (Hughes et al, 2007) and one suggests a strong negative link (Ketola and Saarinen, 2015).…”
Section: Problems With Tolerance Curvesmentioning
confidence: 99%
“…When this information is projected on tolerance curves obtained at constant environments it unambiguously indicates if fitness in fluctuating environments is reflected in the tolerance curves. Ketola and Saarinen (2015) did not utilize marker strains and they used fitness surrogates in their experiments. Still, this study provides insights on the value of tolerance curves obtained from constant thermal environments.…”
Section: Experimental Evolutionmentioning
confidence: 99%
See 1 more Smart Citation